The Right to Work for Person with Disabilities In Indonesia: Legal Protection, Equality, And Social Ecology - Anggriana, Anggita; Nurhidayati , Syssy; Fadhil, Moh. (Widya Pranata Hukum : Jurnal Kajian dan Penelitian Hukum, 2025)
The purpose of this study is to analyze the extent of the legal contribution to the inclusiveness of the work environment to overcome violations of the right to work. The type of research used in this paper is socio-legal research with a statutory approach. The number of workers with disabilities is still very low. This is because there is still stigmatization that places people with disabilities as a marginalized group. The ratification of the Law on Persons with Disabilities is the responsibility of the State after the ratification of the Convention on Persons with Disabilities. The government sets mandatory work quotas as affirmative action. The law also incorporates a social ecology approach ranging from accommodation, and support structures for an equal and inclusive work environment. The government also issued a policy to reward employers who promote and protect the rights of persons with disabilities in their work environment. While Indonesia has made progress, this policy has not been fully implemented at the local government level. A recommendation that needs to be developed is the need for audits of employers to ensure how much the right to work has been fulfilled. .